2013
DOI: 10.1139/cjb-2012-0296
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of arsenic toxicity-induced oxidative damage by coronatine pretreatment in sweet basil (Ocimum basilicum) seedlings

Abstract: Coronatine (COR), a functional analogue of jasmonates, affects the accumulation of defense-related metabolites in plants. However, information on how its effects may be mediated by heavy metal stress is scanty. This study was carried out to determine the changes in some physiological parameters in sweet basil (Ocimum basilicum L.) seedlings pretreated with COR under arsenic (As) toxicity. COR was applied to seedlings at the three-leaf stage at 50 and 100 nanomolars (nmol·L −1 ). Arsenic at 150 and 300 mol·L −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Pretreatment with coronatine improved the toxicity of silver nanoparticles by reducing the H 2 O 2 content. The present findings are in agreement with the results of Zare Dehabadi et al (2013), who indicated that exogenous application of coronatine reduced MDA overproduction in sweet basil seedlings under arsenic stress (Zare Dehabadi et al 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Pretreatment with coronatine improved the toxicity of silver nanoparticles by reducing the H 2 O 2 content. The present findings are in agreement with the results of Zare Dehabadi et al (2013), who indicated that exogenous application of coronatine reduced MDA overproduction in sweet basil seedlings under arsenic stress (Zare Dehabadi et al 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, a decrease in proline content was observed in cress plants exposed to silver nanoparticles, while coronatine treatment mitigated this reduction in proline content induced by silver nanoparticles. Our findings are consistent with the increase in proline observed with coronatine treatment in sweet basil plants under arsenic stress (Zare Dehabadi et al 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Copper is a component of enzymes associated with electron transport and protection against superoxide-free radicals [32]. Arsenic toxicity has been shown to cause an increase in reactive oxygen species leading to membrane leakage [33]. In the current study shoot Cu was reduced by ≥83% and root Cu by 94%.…”
Section: Translocation Percentage and Tissue Concentrationmentioning
confidence: 53%
“…Arsenic exposure causes widespread damage to a number of essential plant functions i.e. electron transport, neutralizing free radicals, photosynthesis, and membrane integrity [33] [34] [39]. Offsets in the timing of when factors controlling detoxification, damage control, and the initiation of secondary systems as primary systems are damaged may result in a complex growth response.…”
Section: Irismentioning
confidence: 99%